Silver Nanoparticle-Based Dressings for Various Wounds: Benefits and Adverse Effects - Phatanodom, Korapin; Angthong, Chayanin (My University, 2024)
Introduction: Silver nanoparticles (AgNP) are a novel therapeutic approach to wound dressings because of their antibacterial properties. Silver has been used throughout history for many purposes. However, evidence-based information about the benefits of AgNP-based wound dressings and potential adverse effects is still required. This study is to comprehensively review the benefits and complications of AgNP-based wound dressings for different wound types and address the knowledge gaps. Material and methods: We collected and reviewed the relevant literature from available sources. Results: AgNP-based dressings have antimicrobial activity and promote healing with only minor complications, making them suitable for several types of wounds. However, we could not identify any reports on AgNP-based wound dressings for common acute traumatic wounds, such as lacerations and abrasions; this includes comparative studies of AgNP-based and conventional wound dressings for such wound types. Conclusions: AgNP-based dressings are beneficial in traumatic, cavity, dental, and burn wounds’ treatment with only minor complications. However, further studies are needed to discern their benefits for specific traumatic wound types.
Keywords: burn wounds; dental wounds; silver nanoparticles; traumatic wounds; wound dressing